Faktor-Faktor Yang Mempengaruhi Korupsi Berdasarkan Teori Fraud Triangle Pada Novel 86 Karya Okky Madasari - Aan Saputra; Hilmy Darul Fadilah; Eva Dwi Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research aims to determine the factors that cause corruption using the fraud triangle theory in literary media. The literary work that will be used as a source of research data is the novel entitled